2022
DOI: 10.1149/2754-2726/ac7c78
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of H2O2Using an Activated Glassy Carbon Electrode

Abstract: Herein, we report the electrochemical sensing of H2O2 in milk samples using an activated glassy carbon electrode (GCE). For this purpose, activation of GCE was carried out in 0.1 M H2SO4 by continuous potential sweeping between -0.7 to 1.8 V for 25 cycles. The activated glassy carbon electrode (AGCE) showed a redox peak at 0.1 V in the neutral medium corresponding to the quinone functional groups present on the electrode surface. The AGCE was studied in (pH 7.4) 0.1 M PBS for the electro-catalysis of H2O2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 65 publications
1
68
0
Order By: Relevance
“…In general, charge transfer resistance (R ct ) of the working electrode is related to the diameter of semicircle which can indicate the interfacial processes of charge transport between the electrode surface and electrolyte ions [38]. In the study, EIS plots are represented by straight lines at lower frequency range whereas semicircles at higher frequency range [39]. The semicircle is formed due to charge transfer and capacitive resistance, while straight line indicates the diffusion resistance characterized by Warburg mass transfer resistance [40].…”
Section: Evaluation Of Electrocatalytic Activity Of Fabricatedmentioning
confidence: 99%
“…In general, charge transfer resistance (R ct ) of the working electrode is related to the diameter of semicircle which can indicate the interfacial processes of charge transport between the electrode surface and electrolyte ions [38]. In the study, EIS plots are represented by straight lines at lower frequency range whereas semicircles at higher frequency range [39]. The semicircle is formed due to charge transfer and capacitive resistance, while straight line indicates the diffusion resistance characterized by Warburg mass transfer resistance [40].…”
Section: Evaluation Of Electrocatalytic Activity Of Fabricatedmentioning
confidence: 99%
“…Furthermore, GNR showed a broad redox peak centered at 0.125 V (E pa ∼ 0.2 and E pc ∼ 0.05 V). This redox peak was observed due to the presence of quinone functional groups on the surface of GNR which was generated during the unzipping process [41,42]. Figure 5(c) (black curve i) showed a notable redox peak at 0.8 V (E pc ∼ 0.65 and E pa ∼ 0.95 V) with high peak currents which were assigned to MnO 2 [43].…”
Section: Surface Morphology Analysismentioning
confidence: 99%
“…The anodic peak currents of GNR/Co 3 O 4 /GCE were increased linearly with the increase of the scanning rate from 10 to 200 mV/ s. The linear equation was established between H 2 O 2 oxidation peak currents and square root of scan rates with a correlation coefficient of (R 2 ) 0.9893 (Figure 4(b)). It was found that H 2 O 2 oxidation on GNR/Co 3 O 4 /GCE was a diffusioncontrolled process [18].…”
Section: Electrochemical Oxidation Of H 2 Omentioning
confidence: 99%
“…Colorimetry and fluorimetry methods are considered to be expensive and may not be suitable for general laboratory use. Electrochemical sensing of H 2 O 2 can be performed by enzymatic and nonenzymatic methods [18,19]. Enzymatic electrochemical sensors are vulnerable to the environmental factors such as temperature, pressure, pH, and biological pathogens [20].…”
Section: Introductionmentioning
confidence: 99%